EFFECTIVENESS OF USING ACTIVATED CARBON TO REDUCE POLLUTANTS IN LEACHATE - Nindy Callista Elvania; Oktavianus Cahya Anggara; Narafa Nur Khairiyyah; Regina Widya Putri L (Jurusan Kimia FMIPA Universitas Lampung, 2025)
Leachate pollution resulting from dissolution process organic and inorganic materials in open landfills is a serious environmental problem. Leachate contains various pollutants, such as heavy metals, organic compounds, and hazardous compounds that can damage water and soil quality not managed properly. This study aims assess the effectiveness activated carbon in reducing pollutants in leachate and factors that affect the performance of activated carbon in leachate treatment. The method used in study is leachate treatment using activated carbon as an adsorbent medium. Testing was carried out with variations in contact time and activated carbon concentration to determine the optimal conditions for pollutant absorption. Water quality parameters tested included COD, BOD, Fe and Zn. The results of study showed that activated carbon is very effective in reducing pollutant content in leachate. This can be seen from results of the effectiveness calculation where it was found that activated carbon can reduce COD 63.96%, BOD 44.89%, Fe 83.33%, and Zn 83.33%.